2017
DOI: 10.7717/peerj.4214
|View full text |Cite
|
Sign up to set email alerts
|

Expression of schizophrenia biomarkers in extraocular muscles from patients with strabismus: an explanation for the link between exotropia and schizophrenia?

Abstract: Recent studies have implicated exotropia as a risk factor for schizophrenia. We determined whether schizophrenia biomarkers have abnormal levels of expression in extraocular muscles from patients with strabismus and explored whether differences in gene expression between medial and lateral rectus muscles may explain the specific association of schizophrenia with exotropia but not esotropia. Samples from horizontal extraocular muscles were obtained during strabismus surgery and compared with age- and muscle typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 94 publications
(136 reference statements)
0
8
0
Order By: Relevance
“…Might this reflect a long‐ago lost atavistic trait? Does the unique molecular repertoire of the lateral rectus relate to the congenital myopathies that are specific to this EOM, for example, some forms of Duane's retraction syndrome (Wahl et al, ; reviewed by: Kekunnaya & Negalur, ) and, as recently hypothesized, a link with schizophrenia (Agarwal et al, )?…”
Section: Early Lineages—multiple Choicesmentioning
confidence: 97%
“…Might this reflect a long‐ago lost atavistic trait? Does the unique molecular repertoire of the lateral rectus relate to the congenital myopathies that are specific to this EOM, for example, some forms of Duane's retraction syndrome (Wahl et al, ; reviewed by: Kekunnaya & Negalur, ) and, as recently hypothesized, a link with schizophrenia (Agarwal et al, )?…”
Section: Early Lineages—multiple Choicesmentioning
confidence: 97%
“…Congenital blindness (or very early loss of vision) has been reported to protect against developing schizophrenia, 64,65 while abnormal vision and/or abnormal early visual experiences (as would be frequent in children with exotropia) appears to be a significant risk factor for schizophrenia. 13 Our findings raise the possibility that exotropia is a risk factor specifically for deficit schizophrenia. The question whether people with deficit schizophrenia have exotropia more often than would otherwise be expected has not yet been tested, but should be explored.…”
Section: (Panel B)mentioning
confidence: 70%
“…Seasonality of births has been extensively studied for schizophrenia, [4][5][6] but one, relatively frequent condition that is a risk factor for schizophrenia, exotropic (outwards) horizontal strabismus, 13 has remained virtually unstudied for seasonal factors. Only one previous study examined seasonality of births in patient populations with horizontal strabismus: a Japanese study in the 1980s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that in some special populations, it would be important to test the visual acuity of each eye independently and also test stereovision, because abnormalities in binocular vision caused by strabismus or other pathologies could explain the inconsistency between previous results and recent studies in depression or autism ( Norton et al, 2016 ; Schauder et al, 2017 ). For example, the rate of strabismus in autistic ( Kaplan et al, 1999 ) and schizophrenic populations ( Agarwal et al, 2017 ; Ndlovu et al, 2011 ; Toyota et al, 2004 ) is higher than in the normal population. Moreover, some studies found a higher rate of strabismus in people with epilepsy ( Jensen & Seedorff, 1976 ; Millar, 1965 ).…”
Section: Discussionmentioning
confidence: 99%